Hubungan antara Regulasi Emosi dengan Perilaku Prososial pada Perawat Rumah Sakit Jiwa Grhasia Yogyakarta - Putri, Dwi Widarna Lita (EMPATHY Jurnal Fakultas Psikologi, 2013)
AbstractThis study aims to determine the relationship between emotion regulation and prosocial behavior of psychiatric hospital nurses. The subjects in this study are nurses in the Grhasia mental hospital, Yogyakarta by the number of subjectâs as many as 115 people, including 45 men and 70 women. Selection of subjects is using study population. study population was all subjects are used as research subjects. Product moment correlation of test results between emotion regulation and prosocial is resulted correlation coefficient of 0.001 with p <0.01. This case shows that there is a positive correlation between emotion regulation and prosocial behavior. Effective donations given by emotion regulation toward prosocial behavior is 14.8% and 85.2% caused by other factors.Keyword: prosocial behavior, emotion regulation.Â